Mathematical modelling and analysis of temperature effects in MEMS based bi-metallic cantilever for molecular biosensing applications - Miranji Katta; Sandanalakshmi R (Kuwait Journal of Science)
As Lab-on-Chip platforms with micro-and nano-dimensions evolve biosensors using miniaturized and high-sensitivity cantilevers are becoming more attractive. Although these sensors function in non-isothermal situations, computational mathematics generally ignores the temperature. Conversely, biosensors can’t be designed with a single-layered cantilever. Yet, in Nano-Electro-Mechanical-Systems, the influence of temperature is more likely to be dominant since the surface-to-volume ratio is higher. In the context of this conclusion, the mathematical modelling comprises temperature and the associated material attributes. This work presents a simple and direct analytical technique for analysing the control of bimetallic cantilevers with NEMS-based sensing and actuation mechanisms. Methodological techniques were used to develop and solve some well-known models of mathematical equations. Parametric analysis data is a major factor in the functioning of all of the other works studied. The findings of FEA comparisons and experiments reveal that the mathematical model's predictions are more than 20% correct.